Development of Blog-Based Partuturon Materials on Local Content Subjects to Improve Children's Cultural Literacy at SD Negeri 200309 Purwodadi Padangsidimpuan - Harahap, Anna Leli; Yulianda, Asri; Nasution, yuannisah Aini (Aksara: Jurnal Bahasa dan Sastra, 2024)
This study aimed to evaluate the effectiveness of blog-based partuturon materials in enhancing cultural literacy among students at SD Negeri 200309. The research employed a Research and Development (R&D) methodology, focusing on product development and effectiveness evaluation in an educational context. The research on blog-based partuturonprovides significant benefits in enhancing cultural literacy by combining the richness of local traditions with modern technology. Through an interactive and easily accessible blog platform, students can learn and appreciate partuturon concepts in a more engaging and relevant manner to their daily digital lives, while simultaneously preserving cultural heritage in a format accessible to future generations.The sample consisted of fifth-grade students at SD Negeri 200390 Purwodadi. Data collection involved pretest and posttest assessments to measure learning outcomes before and after implementing the blog-based materials. Data analysis utilized N-gain calculations to determine the improvement in student performance. Results demonstrated that the developed blog-based partuturon materials effectively enhanced student learning outcomes, with an N-gain of 57% between pretest and posttest scores, indicating a "medium" category improvement. This significant difference in average scores validates the effectiveness of the blog-based approach in improving students' cultural literacy.This means that these results could lead to the development of technology-based curriculum for other cultural subjects, such as traditional arts, local languages, or local history, thus creating an integrated and interactive learning model that can increase student engagement and cross-cultural understanding at different levels of education.Keywords: cultural literacy, blog-based learning, partuturon, elementary education, R&D methodology